Analisis Tingkat Keamanan Sistem Informasi Akademik Berdasarkan Standard ISO/IEC 27002:2013 Menggunakan SSE-CMM - Kurniawan, Endang; Riadi, Imam (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
The objective of this research is to find out the level of information security in the academic information system to give recommendations improvements in information security management. The method used is qualitative research method, which data obtained based on the results of questionnaires distributed to respondents with the Guttmann scale. Based on the analysis results, 13 objective controls and 43 security controls were scattered in 3 clauses. From the analysis, it was concluded that the maturity level of information system security governance was 2.51, which means the level of maturity is still at level 2 but is approaching level 3 well defined.